(untitled) (Journal of Psychiatrists’ Association of Nepal, 2025)
Introduction: Globally, the number of internet users has been increasing every day. In 2021, about 4.9 billion people in the world were using the internet. In India, 622 million people were active internet users in 2020. The figure is higher among the younger population. The study aims to measure the prevalence of Internet addiction among undergraduate medical students and its association with psychological distress. Materials and Methods: A cross-sectional study was conducted among medical students (n = 450) studying at the Jawaharlal Institute of Postgraduate Medical Education and Research, Puducherry, India. The study period was from January 2020 to December 2021. To assess internet addiction and psychological distress, Young’s Internet Addiction Scale and Kessler Psychological Distress Scale were used, respectively. Results: Out of 450 medical students, 39.8% were females and 60.2% were males. There were 45.3%, 29.8%, and 0.9% of students with mild, moderate, and severe internet addiction, respectively. There is a significant positive correlation between internet addiction and psychological distress. Conclusion: The prevalence of internet addiction and psychological distress were found to be high in medical students. However, most of them had a mild to moderate level. Most of the students with severe internet addiction and psychological distress were in their final year, and they were recommended to consult mental health professionals.